Production of Maltooligosaccharides from Black Potato (Coleus tuberosus) Starch by α-amylase from a Marine Bacterium (Brevibacterium sp.) - NANIK RAHMANI; ROHANA ROHANA; SUKARNO SUKARNO; ADE ANDRIANI; YOPI YOPI (Indonesian Society for microbiology, 2013)
High quality maltooligosaccharides were produced from indigenous Indonesian black potato starch by making use of an amylase from Brevibacterium sp. Optimal production was achieved at 2.5% (w/v) substrate concentration, an enzyme-substrate ratio of 1:5 (w/v) and hydrolysis time of 4 h. Under such conditions the yield of reducing sugars was 14 240 ppm with a polymerization degree of 16. Thin layer chromatography (TLC) revealed the formation of glucose, maltose, and maltotriose with Rf values of 0.60, 0.52, and 0.37, respectively. HPLC analysis of freeze-dried samples disclosed Rf values of 0.60, 0.50, 0.37, and 0.12. Maltooligosaccharide profile analysis both using TLC and HPLC showed that the enzymatically hydrolyzed samples contained glucose, maltose, and maltotriose. Thus, black potato starch can be randomly converted into simple sugars and maltooligosaccharides applying by amylolytic enzymes from the marine microbe Brevibacterium sp.